BAHASA KEMBANG KERANG DAYA DALAM PEMBELAJARAN MATEMATIKA SD/MI: The Language Of Kembang Kerang Daya In Primary/MI Mathematics Learning - Munir, Muhammad (Yayasan Al-Amin Qalbu, 2024)
Mathematics is a universal language, but a number of students still experience difficulties in learning it, due to constraints with the language commonly used by students, for example, students' knowledge or understanding of the terms in the context of a given problem is still low. Student language becomes one of the essential things in learning mathematics, in which students are able to use the terms or language they have in defining a mathematical concept. This study aims to explore the language of kembang shells daya which is related to mathematics through exploration with an ethnographic approach. Retrieval of research data is done by interviews and field observations. Based on the theory and results of research that the use of local languages in learning mathematics both in algebra, geometry and measurement materials really helps students in understanding elementary / MI mathematics material